MONITORING KADAR POLUSI UDARA MENGGUNAKAN MICROCONTROLER ARDUINO DAN SENSOR MQ5 - Panulisan, Bambang Setyo; Mansyuri, Umar; Khaerudin, Dedy (LPPM Universitas Bina Bangsa, 2023)
Industrial production processes and motorized vehicles that use fuel oil are the biggest air pollutants. One of the air pollutants is carbon monoxide which is very dangerous when inhaled into the human body in very high concentrations. A plan will then be developed to monitor air pollution around the Uniba Integrated campus using an IoT system. Test data for the MQ 5 carbon monoxide sensor is available. The results of the Sonsor MQ 5 test were carried out for one month at three locations on campus and the highest pollution levels were observed in the parking area